Dissociation Behavior of Methane Hydrate in Porous Media - Zhang Yu; Wu Hui-Jie; Li Xiao-Sen; Chen Zhao-Yang; Li Gang; Zeng Zhi-Yong (2010)
The dissociation behavior of methane hydrate in the porous media were studied when the temperature was above the quadruple phase[Hydrate(H)-Water(L(W))-Ice(I)-Vapor(V)] point temperature. The silica gels were applied as the porous media for the experiments, in which the diameter ranges of the silica gel particles were 0. 105-0. 150, 0. 150-0. 200 and 0. 300-0. 450 mm, and the mean pore diameters, 9. 03, 12. 95, 17. 96 and 33. 20 nm, respectively. The dissociation experiments were carried out by depressurization in the temperature range of 269. 15-278. 15 K and the initial formation pressure range of 4. 1-11. 0 MPa. The experiments indicated that the dissociation rate of methane increases with the increase of the initial formation pressure, the decrease of the bath temperature, the decrease of the particle range and the increase of the mean pore diameter. For relative big the particle diameter, the water in some pores becomes ice in the dissociation process, which makes the dissociation process relatively slow.